Study of the regulation mechanism of calcination temperature on the pozzolanic activity of willow leaf ash - Chaoyu WANG; Tingye QI; Guorui FENG; Song YANG; Haochen WANG; Linfei WANG; Xinyu GAO (工程科学学报, 2023)
As a renewable and clean source, biomass energy is one of the substitutes for traditional fossil energy. However, when biomass is burned as an industrial fuel, it produces a large amount of biomass ash with considerable pozzolanic activity. Currently, the activity of biomass ash is ignored in the utilization of biomass energy. Therefore, research on the regulation mechanism of calcination temperature on the pozzolanic activity of biomass ash will facilitate its efficient utilization. Therefore, we reviewed previous research and selected 500, 700, and 850 ℃ temperatures to calcinate willow leaves. The contents of SiO2, CaO, and other oxides in the willow leaf ash were determined through X-ray fluorescence spectrometer(XRF). The specific surface area of willow leaf ash was determined using a laser particle size analyzer. The mineral composition of willow leaf ash was characterized by X-ray diffraction (XRD), and the characterization of the chemical bonds of the minerals was supplemented by Fourier-transform infrared (FTIR) spectroscopy. The zeta potential of the willow leaf ash–Ca(OH)2 solution was determined through microelectrophoresis to evaluate the system’s stability. After determining the basic physical and chemical properties of willow leaf ash, the mechanical properties of willow leaf ash–cement-based materials were investigated by replacing 20% (mass fraction) cement with the ash, and the factors affecting performance were analyzed. The pozzolanic activity of willow leaf ash at 500, 700, and 850 ℃ was evaluated through the activity index. Rapid evaluation of pozzolanic activity was conducted by active ion extraction capability and inductively coupled plasma-optical emission spectrometer (ICP-OES) analyses. Scanning electron microscopy and XRD characterization methods were combined to analyze the effect of calcination temperature on the structure and composition of the ash and to elucidate the mechanism of the effect of calcination temperature on its pozzolanic activity. The results show that the SiO2 content in the ash was 20% to 30%, and the specific surface area increased with increasing temperature. However, the presence of xonotlite in willow leaf ash was detected through XRD at 850 ℃ Furthermore, the observed FTIR absorption peak at 1120.74 cm−1 corresponded to the stretching vibration of the Si–O–Si structure, which indicated that some amorphous SiO2 was crystallized. The absolute value of the zeta potential of the solution containing willow leaf ash at 500 ℃ and 700℃ was considerably higher than that at 850℃. After replacing a part of the cement with willow leaf ash, the willow leaf ash–cement-based material exhibited the highest compressive strength at 500 ℃ with an activity index of 0.79. The rate of conductivity variation of the willow leaf ash–Ca(OH)2 solution at 500 ℃ and 700 ℃ was higher than that at 850 ℃. The concentration of Si4+ precipitation decreased with the increase in calcination temperature, indicating that willow leaf ash had the highest pozzolanic activity at 500 ℃ followed by 700 ℃. Excessively high calcination temperatures lead to the crystallization of amorphous SiO2 and slagging in willow leaf ash, along with a decrease in the pozzolanic activity. This study provides theoretical support for the regulation of the pozzolanic activity of biomass ash and its applications.